Analisis Penguatan Teori Modal Manusia melalui Studi Literatur tentang Pembiayaan Pendidikan di Berbagai Negara - Kharisatul Ulya; Wahyu Saputra; Khafid Ismail (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This article discusses the strengthening of human capital theory through a literature review of education financing in various countries. Using a qualitative approach based on literature review, this study identifies and analyzes various government and private funding models, as well as partnership schemes, and their implementation in both developed and developing countries. The study's findings indicate that the effectiveness of human capital development is significantly influenced by the sustainability of financing policies, equitable access to education, and fund allocation mechanisms that respond to community needs. The variety of funding models reflects differences in fiscal capacity and policy orientation in each country, but overall, it confirms that investment in education is a strategic instrument in strengthening human capital competitiveness. This study concludes that designing inclusive, adaptive, and long-term education funding schemes is a crucial prerequisite for strengthening human capital theory.